AKTIVITAS FISIK DAN OLAHRAGA BAGI PENDERITA HIPERTENSI - Briliansyah, Muhamad Roofid; Safitri, Erlina Dwi (Journal of Sport Science and Tourism Activity (JOSITA), 2022)
Hypertension or high blood pressure here can also be called "the silent disease" because there are no visible symptoms from the outside. Hypertension here can be categorized into 2 groups in macro type, namely secondary hypertension and primary hypertension. Secondary hypertension is a category of hypertension whose symptoms have been diagnosed initially, then primary hypertension is a category of hypertension whose initial symptoms have not been diagnosed. Treatment methods for people with hypertension aim to lower blood pressure that is continuously increasing without causing significant side effects. One of the therapies is therapy whose method is to make changes in a new lifestyle. To make changes to this new lifestyle, it can be done by maintaining a BMI, regulating sodium consumption, stopping alcohol consumption, quitting smoking, increasing potassium consumption and exercising regularly. One type of physical activity is sports that have a clear plan and structure and involve regular body movements. The goal is to improve physical fitness in the body and avoid the emergence of disease.